2016
DOI: 10.1016/j.celrep.2016.06.073
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a “Pre-mouth Array” from the Extreme Anterior Domain Is Directed by Neural Crest and Wnt/PCP Signaling

Abstract: SUMMARY The mouth arises from the extreme anterior domain (EAD), a region where the ectoderm and endoderm are directly juxtaposed. Here we identify a ‘pre-mouth array’ in Xenopus that forms soon after the cranial neural crest has migrated to lie on either side of the EAD. Initially, EAD ectoderm comprises a wide and short epithelial mass that becomes narrow and tall with cells and nuclei changing shape, a characteristic of convergent extension. The resulting two rows of cells - the pre-mouth array - later spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Concentrations ranging from 50 to 100 µm were effective in causing a persistent buccopharyngeal membrane when the media and inhibitor were refreshed one time at stage 39. Earlier treatments also resulted in embryonic mouth defects, but these may be due to JNK's role in other processes during orofacial development (Jacox et al, ) and are not shown.…”
Section: Resultsmentioning
confidence: 97%
“…Concentrations ranging from 50 to 100 µm were effective in causing a persistent buccopharyngeal membrane when the media and inhibitor were refreshed one time at stage 39. Earlier treatments also resulted in embryonic mouth defects, but these may be due to JNK's role in other processes during orofacial development (Jacox et al, ) and are not shown.…”
Section: Resultsmentioning
confidence: 97%
“…In sea urchins and basal deuterostomes that lack a central nervous system or brain, mouth ectoderm arises from the epidermal layers . In vertebrates, oral ectoderm derives also from the anterior neural ridge (ANR), the front of the neural plate . This dual source of mouth ectoderm is also found in Ciona, an invertebrate chordate, whose mouth is derived from the anterior neuropore .…”
Section: Oral Evolution: Is Mouth Development Conserved?mentioning
confidence: 99%
“…This is EAD ectoderm that will surround the mouth opening and contribute to the oral cavity. Subsequently, a basement membrane forms that separates the developing brain from EAD ectoderm . Overlying epidermal ectoderm can be substituted by flank epidermal ectoderm and is therefore not specific for mouth development .…”
Section: Steps To Form a Mouth: Xenopus As A Paradigmmentioning
confidence: 99%
See 2 more Smart Citations